Atractotomus Fieber 1858 - Duwal, Ram Keshari; Jung, Sunghoon; Yasunaga, Tomohide; Lee, Seunghwan (Zenodo, 2016)
Genus Atractotomus Fieber, 1858 Atractotomous Fieber, 1858: 317 (gen. nov.). Type species: Capsus magnicornis Fallén, 1807; monotypy. 17. Atractotomus morio Sahlberg, 1883 (Figure plate 2) Atractomomus morio J. Sahlberg, 1883: 94 (sp. nov.); Josifov (1992b): 126 (report); Schuh (1995): 267 (cat.); Kerzhner & Josifov (1999): 312 (cat.); Yasunaga (2001a): 155 (diag., figs); Vinokurov et al. (2010): 129 (cat.); Aukema et al. (2013): 285 (cat.). Specimens examined . South Korea : GW : 2♀, Honcheon-gun, Sambong natural forest, 26.vi.2003, J.W. Seong; 2♂, 2♀, Yongdae-ri, Mt. Maebong, Yongdae Natural Recreation Center, 06.vi.2014, on light trap, R.K. Duwal. Distribution . European continent: Finland, Russia (Central, North) Sweden; Asia: North Korea, South Korea * (GW), Mongolia, Russia (East Siberia, Far East, West Siberia) (Josifov 1992b, Kerzhner & Josifov 1999, Aukema et al. 2013). Host . Picea sp. (Pinaceae) (Kerzhner 1988b, Josifov 1992b, Stonedahl 1990). Published as part of Duwal, Ram Keshari, Jung, Sunghoon, Yasunaga, Tomohide & Lee, Seunghwan, 2016, Annotated catalogue of the Phylinae (Heteroptera: Miridae) from the Korean Peninsula, pp. 101-134 in Zootaxa 4067 (2) on page 107, DOI:10.11646/zootaxa.4067.2.1, http://zenodo.org/record/270595